Sprint performance in relation to mechanical properties of the muscle-tendon unit and running track compliance - Stafilidis, S. (2006)
The strain and elongation of the vastus lateralis (VL) tendon, tendon plus aponeurosis, and aponeurosis were examined during maximal voluntary contractions on a Biodex-dynamometer (knee angle: 115°, hip angle: 140°) in twelve sprinters. Following a warm up phase the subjects were instructed to perform a gradual maximal knee extension and hold it for about 3s. The kinematics of the leg were recorded using a Vicon 512 system with 8 cameras operating at 120 Hz. Ultrasonography images were taken simultaneously from the VL myotendinous junction and the mid lateral part of the VL muscle belly. During the maximal isometric knee exte nsions the knee joint rotated (13.6 ±5.9°), leading to an overestimation of the elongation of the tendinous tissues. After correcting for this, the maximal elongation of the VL tendon examined at the myotendinous junction was lower (p<0.05) than the maximal elongation of the VL tendon plus aponeurosis examined at the muscle belly (15 vs. 27 mm respectively). The maximal estimated strains of the tendon, tendon plus aponeurosis, and aponeurosis showed no statistical differences (8 ±2, 8 ±1, and 7 ±2% respectively, p>0.05). It is concluded that the strains of the human VL tendon, VL tendon plus aponeurosis and VL aponeurosis, as estimated in vivo by two dimensional ultrasound during maximal isometric contractions, do not differ from each other. The displacement measured at a cross point in the VL muscle belly is significantly greater compared to that measured at the VL myotendinous junction.